Hubungan komunitas moluska dengan parameter lingkungan di kawasan mangrove Pulau Penyu, Tanjung Benoa, Bali - Sari, Kadek Ayu Puspita; Indrawan, Gede Surya; Atmaja, Putu Satya Pratama (Jurnal Biologi Udayana; Vol 28 No 1 (2024): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2024.v28.i01.p06, 2024)
Mangroves are plants in coastal and estuary areas that are influenced by tides. Mangroves provide essential habitats as spawning, nursery and food sources for various biota, including mollusks. Mollusks have a reciprocal relationship with mangrove plants, play an important role in maintaining the balance of the food chain in mangrove ecosystems. The objective of the research is to establish the structure of the mollusk community and its correlation with environmental conditions in the Pulau Penyu mangroves. The study was carried out in September 2023. The method employed the 1x1m quadrat transect with 15 points per station. Salinity, pH, temperature and substrate type are all measurements of environmental conditions. The research revealed 24 species, including 20 gastropod species and 4 bivalvia species from 12 mollusk families. Families found include Potamididae, Cerithiidae, Batillariidae, Ellobiidae, Mitridae, Neritidae, Littorinidae, Naticidae, Muricidae, Veneridae, Cyrenidae and Corbulidae. Mollusk abundance ranged from 0,07 to 13,07 ind/m 2 at the research site, with Cerithium coralium being the most abundant species and Corbula macgillivrayi being the least abundant. The results of diversity index is 1,90 to 2,25; evenness index is 0,68 to 0,78; dominance index is 0,18 to 0,25; indicating moderate species diversity, high individual numbers each species, and no dominant species. The range of environmental parameter values obtained were; temperature ranges from 34,1 to 35,37 o C; pH ranges from 6,43 to 6,68; and salinity ranges from 35,2 to 36,3 ppt. The substrate type at the research site was sandy clay and clayey sand. PCA analysis results indicate a strong relationship between mollusk abundance and pH, salinity and sand fraction, but very weak relationship with temperature, dust and clay fraction.